2009
DOI: 10.1007/s00167-009-0942-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteochondral lesions of the talus: a systematic review

Abstract: The aim of this study was to summarize all eligible studies to compare the effectiveness of treatment strategies for osteochondral defects (OCD) of the talus. Electronic databases from January 1966 to December 2006 were systematically screened. The proportion of the patient population treated successfully was noted, and percentages were calculated. For each treatment strategy, study size weighted success rates were calculated. Fifty-two studies described the results of 65 treatment groups of treatment strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
511
1
26

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 547 publications
(544 citation statements)
references
References 62 publications
6
511
1
26
Order By: Relevance
“…This can be accomplished, on the one hand, by fibrocartilaginous repair tissue, e. g. after micro-fracturing or retrograde drilling of osteochondral lesions, or via transplant, using osteochondral autograft transfer (OATS) or the matrix-induced autologous chondrocyte transplantation (MACT) [27,44]. In addition, micro-fracturing can be combined with matrix implantation as part of autologous matrix-induced chondrogenesis (AMIC) at the ankle joint; [19] provides a current overview of this.…”
Section: Assessment Of Therapeutic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be accomplished, on the one hand, by fibrocartilaginous repair tissue, e. g. after micro-fracturing or retrograde drilling of osteochondral lesions, or via transplant, using osteochondral autograft transfer (OATS) or the matrix-induced autologous chondrocyte transplantation (MACT) [27,44]. In addition, micro-fracturing can be combined with matrix implantation as part of autologous matrix-induced chondrogenesis (AMIC) at the ankle joint; [19] provides a current overview of this.…”
Section: Assessment Of Therapeutic Resultsmentioning
confidence: 99%
“…They have a singular age distribution between 15 and 35 years, and 63 % of the patients are male [27]. The osteochondral lesions occur predominantly in the talus with a ratio of occurrences in the tibial plateau to the talar dome of 1 to 20.…”
Section: Classification Of Osteochondral Lesionsmentioning
confidence: 99%
“…The treatment traditionally consists of one or more regimens, which include rest, restriction of activities, immobilization, and non-steroidal anti-inflammatory drugs (NSAIDs). A systematic review by Zengerink et al [4] reported that 45% of patients had successful outcomes when conservatively treated with a weightbearing as tolerated protocol. The authors also demonstrated that 53% of patients who underwent cast immobilization for a duration of 3 weeks to 4 months reported successful clinical outcomes.…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…This procedure is low cost, technically undemanding, and minimally invasive. Several clinical studies have shown that approximately 85% of patients that underwent BMS reported good-toexcellent clinical results at short-and mid-term outcomes [1,4,13]. Two studies have shown the long-term results of BMS.…”
Section: Reparative Proceduresmentioning
confidence: 99%
See 1 more Smart Citation